The triumvirate approach to systems engineering, technology management and engineering management : the art and science of combining systems engineering, technology management and engineering management, using project management as a tracking tool, to create, manage and disseminate the next generation of technology solutions /: the art and science of combining systems engineering, technology management and engineering management, using project management as a tracking tool, to create, manage and disseminate the next generation of technology solutions. (2022) - Day, Thomas J
No abstract available